Construct validity of the self-report instrument of perceived stress in the general Costa Rican population of retirement age: CRELES study - Méndez-Chacón, Ericka (Frontiers in Public Health, 2025)
BackgroundIt is known that the effects of stress on the body harm health and mortality outcomes. Applying self-report instruments to the general population can help identify degrees of stress and provide evidence on how stress affects social relationships, health, and even mortality. This research aims to explore the internal validity of questions of perceived stress in the general Costa Rican population close to pension or retirement age.MethodsA nationally representative sample of 1,469 individuals born between 1945 and 1955 in Costa Rica completed a series of questions related to perceived stress. Factor analysis, elements of classical test theory, and a Rasch model were used to generate evidence of scale validity.ResultsAdequate internal consistency was obtained by factor analysis, with one factor explaining the whole of the variability. The Omega Index value was 0.6261. The fit values (INFIT) detected by the Rasch model range between 0.9 and 1.2.ConclusionThe items form a scale that refers to the construct of perceived stress and has sufficient internal consistency. However, it is imperative to generate a more substantial number of items to enhance this construct’s precision of measurement.